2004
DOI: 10.1007/s00477-002-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Eulerian spatial moments for solute transport in three-dimensional heterogeneous, dual-permeability media

Abstract: A Eulerian analytical method is developed for nonreactive solute transport in heterogeneous, dualpermeability media where the hydraulic conductivities in fracture and matrix domains are both assumed to be stochastic processes. The analytical solution for the mean concentration is given explicitly in Fourier and Laplace transforms. Instead of using the fast fourier transform method to numerically invert the solution to real space (Hu et al., 2002), we apply the general relationship between spatial moments and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This method is also compared with the stationary transport theory developed by Xu and Hu [2004a] for predicting spatial moments of mean concentration. The comparison indicated that the two methods matched very well in predicting first and second spatial moments of mean concentration.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…This method is also compared with the stationary transport theory developed by Xu and Hu [2004a] for predicting spatial moments of mean concentration. The comparison indicated that the two methods matched very well in predicting first and second spatial moments of mean concentration.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…To compare solute transport in stationary flow fields with the previously used stationary transport theory, we compare the spatial moments of mean concentration calculated by NEMM with results obtained from the analytical method [ Xu and Hu , 2004a]. After conducting this comparison, we analyze the influence of several parameters on concentration moments under stationary cases.…”
Section: Illustration Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moments are mathematical tools that can be used to analyze the shape of spatial/temporal signals. They have been used for a variety of purposes, including studies of solute breakthrough curves in soils, e.g., in Stagnitti et al (2000); the behavior of fractional advection-diffusion equations (see Zhang 2010); mixing in heterogeneous porous media (see Chiogna et al 2011); model parameter estimations from column experiments, e.g., in Young and Ball (2000); and analytical solutions in dual-permeability media in Xu and Hu (2004).…”
Section: Preliminaries and Definitionsmentioning
confidence: 99%